Kajian Sektor Unggulan dan Transformasi Struktur Perekonomian di Kabupaten Sleman DIY - Budi Widayanto (Jurnal Dinamika Sosial Ekonomi, 2000)
Regional development in Sleman regency based on its regional potential can be seen from leading sector performance in economy structure Sleman regency using Input-Output (1-0) Analysis. 1-0 Analysis used non-survey method with RAS technique. Development with stressing leading sector as forward wisdom anticipation needs a guidance of the available trend from economy structure transformation. The resulting information base on 1-0 Analysis that agriculture sector was the leading sector with surplus level at 8 rank (3,80), leakage level at 5 rank (3,36) and domestic output (Rp. 647.416 millions) higher than demand quantity (Rp. 584,429 millions) indications The forward wisdom must be adjusted with the trend of the economy structure transformation, especially since 1994 the relative share of services sector and manufacture industry more higher than the relative share of agriculture sector.Key words: Regional development. 1-0 tabel, agriculture sector, structure transformation.